2018
DOI: 10.1002/lom3.10255
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of methylamines in seawater using solid phase microextraction and gas chromatography

Abstract: The methylamines form part of the marine organic nitrogen pool. Although they are ubiquitous in marine systems, little is known about their distribution, production, and fate in the marine environment. Analytical methods have been developed for their analysis in marine waters, but these have employed custom‐made apparatus, limiting data to a few studies. Here, we report a method developed for the determination of methylamines in seawater which combines headspace solid phase microextraction (SPME) and gas chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…Briefly, the ART-2a area matrix (AM) of a single particle mass spectra reppresents the average intensity for each m/z for all particles within a group, reflecting the typical mass spectra of specific aerosol groups. (mono-, di-and trymethylamines) were extracted from the water sample by solid phase microextraction 34 , where polydimethylsiloxane/divinylbenzene fibre was exposed in the headspace above the water sample, for 2.5 h at 60 o C. Methylamines were resolved and detected using a GC with NP detector, calibrations carried out using external matrix-matched standard solutions containing mono-, di-and trimethylamine (0.13-13.3 nM).…”
Section: Atofmsmentioning
confidence: 99%
“…Briefly, the ART-2a area matrix (AM) of a single particle mass spectra reppresents the average intensity for each m/z for all particles within a group, reflecting the typical mass spectra of specific aerosol groups. (mono-, di-and trymethylamines) were extracted from the water sample by solid phase microextraction 34 , where polydimethylsiloxane/divinylbenzene fibre was exposed in the headspace above the water sample, for 2.5 h at 60 o C. Methylamines were resolved and detected using a GC with NP detector, calibrations carried out using external matrix-matched standard solutions containing mono-, di-and trimethylamine (0.13-13.3 nM).…”
Section: Atofmsmentioning
confidence: 99%
“…Further analyses of water samples were performed at the University of Plymouth, UK, using solid phase microextraction, gas chromatogpaphy and nitrogen phosphorous detection (SPME-GC-NPD) according to Cree et al, (2018). In brief, 850 mL of the acidified filtered sample was adjusted to pH 13.4 with sodium hydroxide solution (10 M) to convert the amines to their gaseous form.…”
Section: Amine Measurements In Seawatermentioning
confidence: 99%
“…Cree (2014) found that 7 of 10 primary pigments also correlated positively with GBT, including fucoxanthin, while a close relationship of both GBT and chl-a with phytoplankton carbon was observed. Although bacteria may be the primary source of methylamines in the water column (Lidbury et al, 2014;Lidbury et al, 2015a;2015b;Jameson et al, 2016), their short residence time (Cree et al, 2018) indicates that both phytoplankton and bacteria play a role in methylamine abundance and dynamics.…”
Section: Amines In Seawatermentioning
confidence: 99%
“…More recently, Cree et al reported another method to determine dissolved methylated amines in seawater samples. Methylated amines converted to the gaseous phase were analysed by coupling headspace solid phase microextraction (SPME) and gas chromatography coupled with a nitrogen-phosphorus detector (GC-NPD) (Cree et al, 2018). This method provides lower detection limits and is more suitable for measuring methylated amines at low-nM level in marine environments.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 99%